Peran Lain-lain PAD yang Sah dengan Dana Alokasi Umum dan Khusus terhadap Belanja Modal: Perspektif Teori Fiskal Federalism - Juryani Hermalingga; Syahril Djaddang; Nurmala Ahmar (STIM LASHARAN JAYA MAKASSAR, 2017)
The general objectives of this study are to analyze and prove the role of Other Legitimate PAD, local taxes, general allocation funds and special allocation funds to capital expenditures at district / municipal governments in Java. The research object of regency / municipality government in Java Island is 108 regencies/municipalities especially related to factors influencing capital expenditure. This research is quantitative research. The type of data used is secondary data in the form of realization report of district / municipal government budget in Java. The results of this study proves that the higher the revenue of local origin, including the revenue derived from local taxes, the higher the capital expenditure. Local taxes make the largest contribution to local revenue revenues so as to influence regional expenditures including capital expenditures. Other legitimate PAD, although included in the PAD component, but has not been able to moderate local taxes with capital expenditures, this happens because the share of income of other legitimate PAD is relatively small compared to local taxes. The contribution of this research is to the district / municipality government in Java Island realizing the creation of regional autonomy in the Federalist Fiscal Theory Perspective while for the Central Government; This research is expected to be used as an analytical material in the formulation of policies on central and regional financial balances and serve as an analysis material to assess the performance and supervision of local government financial management.